Map of Manitoba, Saskatchewan and Alberta [Central] - White, James, 1863-1928 (Cartographer); Young, R. E. (Surveyor) (Department of the Interior, 1905)
This map shows lands disposed of, homesteads and First Nations reserves in the Prairies in 1905. Consists of 3 map sheets - East, Central and West [see also records for the East and West parts]. "Special edition showing even-numbered sections finally disposed of" Scale 1:792,000, or 12.5 miles to 1 inch. Relief shown by spot heights. Shows land distribution, railways, cities and towns. Preliminary edition. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .